The complete mitochondrial genome of the long-horned caddisfly Triaenodes tardus (Insecta: Trichoptera: Leptoceridae) - Melanie M. L. Lalonde; Jeffrey M. Marcus (Mitochondrial DNA. Part B. Resources, 2017)
The long-horned caddisfly Triaenodes tardus Milne, 1934 (Leptoceridae), is a widespread herbivorous North American caddisfly found in both lentic and lotic habitats. Whole genome Illumina sequencing allowed the assembly of a complete circular mitogenome of 14,963 bp from T. tardus consisting of 73.4% AT nucleotides, 22 tRNAs, 13 protein-coding genes, two rRNAs and a control region in the ancestral insect gene order. Triaenodes tardus COX1 features an atypical TTG start codon as in some lepdioptera and prokaryotes. Phylogenetic reconstruction places T. tardus as sister to Sericostoma personatum (Sericostomatidae) within a monophyletic Order Trichoptera, which is consistent with previous phylogenetic hypotheses.